Study on analysis of gender trends among the first authors of publications on Kawasaki disease - Patel, Heena; Bennet, Cynthia; Muskawad, Sakshi; Shareef, Amina; Khan, Muzamil; Kaur, Snehdeep (International Journal of Advances in Medicine, 2024)
Background: Kawasaki disease is an inflammatory disorder predominantly affecting children less than 5 years of age. If left untreated, it has the potential to cause life-threatening cardiac complications. There have been numerous articles published on it concerning various aspects of the disease over the last 20 years. Thus, the study aims to compare the number of male and female first authors for published Kawasaki disease articles and study whether there is any association between gender and country. Methods: This is a cross-sectional observational study wherein published articles on Kawasaki disease over the last 20 years were assessed and the names of their first authors determined. Subsequently, NamSor was used to establish the gender of the first author. ARIMA (Auto Regressive integrated moving average) was used for statistical analysis. Results: Data evaluation demonstrated that 51% were male first authors, 36% were female first authors, and 12% did not have a clearly determined gender. Males as first authors have been unwaveringly higher in number than females annually. When gender trends are compared globally, there is a statistically significant association between gender and country, with Greece and Finland having the highest female-to-male ratios. Conclusions: Although recent years have seen an increase in the number of female first authors, gender disparity still continues to prevail in medical research. This gap has to be eliminated in order to gain dynamic insight from all genders, which can help form a better understanding and further the cause of innovation in not just Kawasaki disease but any other subject of discussion.